2022
DOI: 10.7150/ijbs.71519
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA APCDD1L-AS1 due to DNA hypermethylation and loss of VHL protein expression promotes the progression of clear cell renal cell carcinoma

Abstract: Background: The current studies only indicated that long non-coding RNA (lncRNA) APCDD1L-AS1, as a novel lncRNA, may play a role in oral squamous cell carcinoma and lung cancer. However, its potential role in clear cell renal cell carcinoma (ccRCC) and its possible mechanism of action remain vague. Methods: TCGA-KIRC and GEO data and qRT-PCR and pyrosequencing results of clinical specimens were used to identify the expression level and DNA methylation status of APCDD1L-AS1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Previous studies have revealed that the abnormal expression of APCDD1L‐AS1 was related to the tumor growth and metastasis, prognosis, and drug resistance in clear cell renal cell carcinoma, lung adenocarcinoma and squamous cell carcinoma, and oral squamous cell carcinoma. 34 , 35 , 36 , 37 MIR210HG is located at 11p15.5 which is associated with tumor cell proliferation and metastasis in endometrial cancer, breast cancer, cervical cancer, NSCLC, and gastric cancer. 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 RP11‐21 L19.1 located in 11p15.2, and the low expression of which was significantly related with a poor prognosis in kidney renal papillary cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that the abnormal expression of APCDD1L‐AS1 was related to the tumor growth and metastasis, prognosis, and drug resistance in clear cell renal cell carcinoma, lung adenocarcinoma and squamous cell carcinoma, and oral squamous cell carcinoma. 34 , 35 , 36 , 37 MIR210HG is located at 11p15.5 which is associated with tumor cell proliferation and metastasis in endometrial cancer, breast cancer, cervical cancer, NSCLC, and gastric cancer. 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 RP11‐21 L19.1 located in 11p15.2, and the low expression of which was significantly related with a poor prognosis in kidney renal papillary cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…APCDD1L‐AS1 located in 20q13.32. Previous studies have revealed that the abnormal expression of APCDD1L‐AS1 was related to the tumor growth and metastasis, prognosis, and drug resistance in clear cell renal cell carcinoma, lung adenocarcinoma and squamous cell carcinoma, and oral squamous cell carcinoma 34–37 . MIR210HG is located at 11p15.5 which is associated with tumor cell proliferation and metastasis in endometrial cancer, breast cancer, cervical cancer, NSCLC, and gastric cancer 38–45 .…”
Section: Discussionmentioning
confidence: 99%
“…Within ccRCC, specific genes undergoing DNA hypermethylation contribute to the promotion of cancer growth and metastasis. Notably, this includes the downregulation of lncRNA ZNF582-AS1 and lncRNA APCDD1L-AS1, both of which exert regulatory control over the progression of ccRCC [40,41]. In colorectal cancer, elevated methylation of TMEM25 exhibits an inverse correlation with its expression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressing APCDD1L-AS1, a novel lncRNA, inhibited the growth and metastasis of ccRCC cells in vitro and in vivo . Dysregulation of histone expression caused by APCDD1L-AS1 overexpression may also inhibit ccRCC progression ( 40 ). However, APCDD1L-AS1 expression was decreased by DNA hypermethylation and inactivation of von Hippel Lindau (VHL) protein expression.…”
Section: Discussionmentioning
confidence: 99%